Feeding practices and availability of storage space for feed and fodder in Gaushalas of Haryana - SUBHASH CHANDRA; M L KAMBOJ; MAN SINGH; RAHUL SINGH; S S LATHWAL (Indian Journal of Animal Sciences, 2022)
The present investigation was carried out to study the existing feeding practices and its storage space in Gaushalas. The data collected from 30 Gaushalas were divided into three categories: small (T1), medium (T2) and large size (T3) Gaushalas. The obtained finding showed that the availability of green fodders was significantly (P<0.05) higher in T3 Gaushalas as compared to T1 Gaushalas. The concentrate mixture was offered to milch cow was significantly (P<0.05) higher in T3 Gaushalas (1.65±0.11 kg/cow) as compared to T2 and T1 Gaushalas (1.29±0.10 and 0.70±0.12). Percentage of shortfall of storage space for dry fodders was highest in T1 Gaushala (-57.29%,) while percentage of shortfall of storage space for concentrate mixture was higher in T3 Gausalas (-30.61%) than T2 Gaushalas (-16.90%). It could be concluded that the better feeding practices and also better availability of storage facilities (dry fodder) is present in T3 Gaushalas.